Cáncer diferenciado de tiroides, de la biología molecular a la clínica - Pineda B., Pedro; Osorio G., Fernando (Revista Hospital Clínico Universidad de Chile, 2011)
Recent advances in molecular research have made possible to identify intracellular pathways involved in cell proliferation and differentiation processes, and to clarify how functional alterations in these pathways could explain development of differentiated thyroid cancer. This information has direct implications in diagnostic and therapeutic strategies. We present a review of this topic with this integrated vision between molecular findings and clinical management.